Polymorphisms of COMT Val158Met and DAT1 3′-UTR VNTR in Illicit Drug Use and Drug-Related Psychiatric Disorders. (19th September 2014) - Chen, Chih-Ken; Lin, Shih-Ku; Chiang, Shu-Chuan; Su, Lien-Wen; Wang, Liang-Jen
<x xml:space="preserve">Abstract</x> To investigate the involvement of COMT Val158Met and DAT1 3′-UTR VNTR genotypes in the pathogenesis of illicit drug use and drug-induced psychotic disorders (DIP), 187 substance users and 386 normal controls were recruited from Northern Taiwan. Substance users and normal controls significantly differed in allele frequencies of COMT Val158Met (p = 0.039) but not in allele frequencies of DAT1 3′-UTR VNTR (p = 0.879). However, neither allele frequencies of COMT Val158Met nor allele frequencies of DAT1 3′-UTR VNTR were associated with DIP. The findings should be confirmed in further studies of a larger sample size and a more homogenous patient group.